Sistem Pendidikan di Arab Saudi dan Perbandingannya dengan Sistem Pendidikan di Indonesia - Rahmadhani, Saszlin; Wahyudi, Hakmi; Anuhgra, Yudha Okta; Suriyah, Suriyah (Lembaga penelitian dan pengabdian kepada masyrakat, 2023)
This paper describes education in Saudi Arabia and how education in Saudi Arabia compares with education in Indonesia. The method used is a literature study. The education system implemented in Saudi Arabia certainly has differences from the education system implemented in Indonesia. For example, the education system in Saudi Arabia puts forward Islamic values because Saudi Arabia is a country that highly upholds syar'i values. Although Indonesia has not implemented an Islamic education system as a whole, Islamic values are still taught in schools. Regarding the curriculum, Saudi Arabia adopts the curriculum from other Arab countries such as Egypt and always develops the existing curriculum so that it doesn't change too much. This is different from Indonesia, which changes the curriculum quite often so that sometimes educators find it difficult to adapt to the new curriculum. These are some of the examples presented in this article. But the most important thing is that both Saudi Arabia and Indonesia always strive to achieve their educational goals, namely to prepare a virtuous and skilled generation in the effort to develop a better nation because education is the most powerful weapon to change the world.